Terrestrial gastropods (Helix spp) as sentinels of primary DNA damage for biomonitoring purposes: A validation study. (26th February 2013) - Angeletti, Dario; Sebbio, Claudia; Carere, Claudio; Cimmaruta, Roberta; Nascetti, Giuseppe; Pepe, Gaetano; Mosesso, Pasquale
<x xml:space="preserve">Abstract</x> We validated the alkaline comet assay in two species of land snail (Helix aspersa and Helix vermiculata) to test their suitability as sentinels for primary DNA damage in polluted environments. The study was conducted under the framework of a biomonitoring program for a power station in Central Italy that had recently been converted from oil to coal‐fired plant. After optimizing test conditions, the comet assay was used to measure the % Tail DNA induced by in vitro exposure of hemocytes to different concentrations of a reactive oxygen species (H2O2). The treatment induced significant increases in this parameter with a concentration effect, indicating the effectiveness of the assay in snail hemocytes. After evaluating possible differences between the two species, we sampled them in three field sites at different distances from the power station, and in two reference sites assumed to have low or no levels of pollution. No species differences emerged. Percent Tail DNA values in snails from the sites near the power station were higher than those from control sites. An inverse correlation emerged between % Tail DNA and distance from the power station, suggesting that the primary DNA damage decreased as distance increased away from the pollution source. Detection of a gradient of heavy metal concentration in snail tissues suggests that these pollutants are a potential cause of the observed pattern. The comet assay appears to be a suitable assay and Helix spp. populations suitable sentinels to detect the genotoxic impact of pollutants. Environ. Mol. Mutagen. 54:204–212, 2013. © 2013 Wiley Periodicals, Inc.